2015
DOI: 10.1016/j.ihj.2015.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Subvalvular apparatus and adverse outcome of balloon valvotomy in rheumatic mitral stenosis

Abstract: It is important to assess the degree of SVA pathology in the conventional echocardiographic assessment for RMS, as BMV would have adverse events when both SVAs were severely diseased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…Subvalvular pathology did not result in sub optimal outcomes after PBMV which was contrary to the findings of Parag Bhalgat et al who studied 356 patients who had undergone PTMC for valvular stenosis or restenosis (14). This bias is due to excluding patients with severe sub valvular disease in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Subvalvular pathology did not result in sub optimal outcomes after PBMV which was contrary to the findings of Parag Bhalgat et al who studied 356 patients who had undergone PTMC for valvular stenosis or restenosis (14). This bias is due to excluding patients with severe sub valvular disease in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…In another study by Vahanian et al who studied 189 patients, >2+ MR developed in 7% of patients (14). A large series from India by Kaul UA et al, reported that 8.4% developed >2+ MR ,of which 3.3% patients developed severe MR and required MVR (16).…”
Section: Discussionmentioning
confidence: 99%
“…Actually rheumatic MV repair is a better procedural strategy than replacement in patients with feasible repair structure, outcome of MV repair is widely verified better than MV replacement and successful durable repairs have been performed in highvolume, expert centers (23). Severe diseased subvalvular apparatus and AF (24) can adversely affected the result of the intervention procedure, MV repair is an optimal strategy for these patients even if the WS <8.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the risk of pulmonary edema extends for several days after delivery . Mortality in Class IV NYHA heart failure is high reaching up to 15–20% …”
Section: Introductionmentioning
confidence: 99%
“…Safety of BMV in pregnant patients has been published . However severe sub valve disease and high Wilkin's score (>8‐10) often results in sub optimal outcomes . We sought to study the outcomes of BMV in pregnant patients with severe sub valve disease and who are severely ill with decompensated heart failure.…”
Section: Introductionmentioning
confidence: 99%